ANALISIS KADAR ARSEN (As) DAN TIMBAL (Pb) PADA MINYAK GORENG PEMAKAIAN BERULANG DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Aminah Aminah; Rahmawati Rahmawati; Tadjuddin Naid; Salma Salma (As-Syifaa Jurnal Farmasi, 2017)
This study aims to analyze the levels of arsenic (As) and lead (Pb) in frying oil usage over and over. This research was conducted at the Center for Health Laboratory Makassar. Samples obtained from merchants fried foods. To ensure the metal content of the samples prior didestruksi with HNO3P and heated for 16 hours to liberate arsenic and lead from the oil matrix, then measured using atomic absorption spectrophotometer (AAS) at a wavelength of 193.7 nm (Arsenic) and 283 nm (lead ). From the results obtained penilitian arsenic (As) in the three vendors that is <0.1 ppm (max 0.1 ISO ppm) and lead levels that merchants 1 (0.1503 mg / kg and 0.1940 mg / kg), traders 2 (0.3452 mg / kg and 0.4005 mg / kg), the merchant 3 (0.1111 mg / kg and 0.1788 mg / kg) respectively for the samples before and after frying (SNI max 0.1 mg / kg).